The Value Of Digital Economy Adoption In Bangka Belitung SMEs: A Vam Model Focusing On Creativity And Innovation - Amri, Amri; Mohamad Makrus; Hidayat Febiansyah; Yulianti, Yulianti (SEAN Institute, 2024)
The adoption of the digital economy by Small and Medium Enterprises (SMEs) in archipelagic regions such as Bangka Belitung has become a crucial focus in efforts to enhance local competitiveness and economic growth. This study aimed to analyze the factors influencing digital economy adoption by SMEs in Bangka Belitung, with a specific focus on the roles of creativity, innovation, perceived benefits, and ease of use, as well as their impact on SME performance. The research employed a quantitative approach with a cross-sectional design. The sample consisted of 399 SMEs in Bangka Belitung, selected using the Slovin formula with a 5% error rate. Data collection was conducted through online and offline surveys using structured questionnaires. The research model was based on the integration of the Value Added Model (VAM) with elements of the Technology Acceptance Model (TAM) and Diffusion of Innovation Theory. Data analysis using SPSS version 26 revealed that creativity, innovation, perceived benefits, and ease of use had positive and significant effects on digital economy adoption. Perceived ease of use had the strongest influence. Digital economy adoption was proven to have a positive impact on SME performance, particularly in terms of increased sales volume and market share. This study provides a theoretical contribution by expanding the understanding of technology adoption in the context of SMEs in archipelagic regions. Practically, these findings highlight the importance of developing creativity, innovation, and education about the benefits and ease of use of digital technology for SMEs. In conclusion, this study affirms the importance of digital economy adoption for SMEs in Bangka Belitung and provides a basis for policy development supporting the digital transformation of SMEs in archipelagic regions.